Loss of meal-induced decrease in plasma ghrelin levels in patients with anorexia nervosa - Nedvídková, Jara; Krykorková, Ivana; Barták, Vladimír; Papezová, Hana; Gold, Philip W; Alesci, Salvatore; Pacak, Karel (The Journal of clinical endocrinology and metabolism, 2003)
Studies have shown that ghrelin plays a major role in energy homeostasis and modulation of feeding behavior. However, little is known about the influence of food consumption on plasma ghrelin levels in humans. Therefore, we investigated responses of plasma ghrelin to food intake, meal volume and meal nutritional value in healthy volunteers and women with anorexia nervosa (AN). After overnight fasting, all subjects received either a standardized breakfast or fiber. Plasma ghrelin levels were measured before and after the meal. Fasting plasma ghrelin was significantly higher in AN patients than in controls (1,800.6 +/- 47.0 vs. 795.9 +/- 24.3 pg/ml, P < 0.001) (606.8 +/- 15.8 vs. 268.2 +/- 8.2 pmol/l, P < 0.001), and correlated negatively with percentage of body fat in both groups. Ghrelin levels markedly fell after consumption of either a standardized meal or fiber in controls, but not in anorexic women. Thus, we concluded that the acute plasma ghrelin response to food intake, which in healthy individuals is independent of meal caloric value, is impaired in women with AN. This abnormality may be part of a chronic adaptation to prolonged food restriction, which attempts to restore a normal feeding conduct by maintaining the drive to eat.
Keywords: dospělí; peptidové hormony; Female; ghrelin; Dietary Fiber; energetický příjem; Adult; ženské pohlaví; Food; nutriční hodnota; lidé; Energy Intake; Nutritive Value; mentální anorexie; Humans; omezení příjmu potravy; složení těla; Ghrelin; Peptide Hormones; Body Composition; Anorexia Nervosa; tuková tkáň; Fasting; potraviny; potravní vláknina; Adipose Tissue